2018
DOI: 10.1074/jbc.m117.803411
|View full text |Cite
|
Sign up to set email alerts
|

HspB1 and Hsc70 chaperones engage distinct tau species and have different inhibitory effects on amyloid formation

Abstract: The microtubule-associated protein tau forms insoluble, amyloid-type aggregates in various dementias, most notably Alzheimer's disease. Cellular chaperone proteins play important roles in maintaining protein solubility and preventing aggregation in the crowded cellular environment. While tau is known to interact with numerous chaperones, it remains unclear how these chaperones function mechanistically to prevent tau aggregation and how chaperones from different classes compare in terms of mechanism. Here, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 59 publications
(86 reference statements)
8
92
0
Order By: Relevance
“…This study showed that Hsp70 slows down the nucleation process of tau, stabilises oligomeric species and inhibits their growth into fibrils . Similar findings were made in a second study, comparing the action of Hsp70 and a second chaperone, HspB1, on K18 and full‐length tau aggregation using FCS and NMR .…”
Section: Tau Oligomers and Filamentssupporting
confidence: 80%
“…This study showed that Hsp70 slows down the nucleation process of tau, stabilises oligomeric species and inhibits their growth into fibrils . Similar findings were made in a second study, comparing the action of Hsp70 and a second chaperone, HspB1, on K18 and full‐length tau aggregation using FCS and NMR .…”
Section: Tau Oligomers and Filamentssupporting
confidence: 80%
“…A 3.4-Å resolution cryo-electron microscopy structure of the common protofilament core of tau filaments purified from an individual with Alzheimer’s disease (PDB ID 5O3L) shows a 306-VQI-308 motif at the start of the first ordered beta sheet [60]. Recent NMR data revealed HspB1 to interact with this region of tau, consistent with binding of substrate IXI/V motifs to sHsp β4/β8 pockets [61]. In such a mechanism of sHsp chaperone action, activity towards these fibril-forming sequences will be modulated by the structural dynamics of both sHsp assembly and the substrate.…”
Section: Discussionmentioning
confidence: 82%
“…It is possible that the same mechanism for rapid, promiscuous recognition of binding partners by IDPs is responsible for the heightened activity of partially unfolded chaperones. Recent reports have indicated that HSP27 interacts with substrates αsynuclein and Tau in a dynamic, transient manner 64,65 with CSPs induced by Tau binding identified in the β6 + 7 strand of cHSP27 65 . Interestingly, many of the residues that are unfolded in the HSP27 monomer are charged or polar (Fig.…”
Section: Discussionmentioning
confidence: 99%